Rapid, sensitive structure analysis of oligosaccharides - Zhao, Yingming (The National Academy of Sciences of the USA, 1997)
We have developed an efficient method for the derivatization of oligosaccharides, wherein the oligosaccharide is efficiently ligated to a basic aminooxyacetyl peptide by oxime formation. The resulting glycopeptide yields much higher sensitivity in matrix-assisted laser desorption/ionization mass spectrometry than does the underivatized oligosaccharide. Digestion of the glycopeptide by a exoglycosidase array and subsequent mass spectrometric assay of the digestion products provide a sensitive and rapid way to elucidate the structure of the oligosaccharide. In addition to oligosaccharide sequencing, the ligation reaction between an oligosaccharide and an aminooxyacetyl peptide also provides a potentially very convenient and efficient way for the synthesis of glycopeptides or glycoproteins.